Creating spaces of learning in academia: fostering niches for professional learning practice. Issue 2 (4th May 2022) - MacDonald, Katrina; Diamond, Fleur; Wilkinson, Jane; Sum, Nicola; Longmuir, Fiona; Kaukko, Mervi
ABSTRACT: This paper analyses the move by an Australian university faculty to a new building featuring open plan and alternative workspaces. Through the lens of the theory of practice architectures, the paper examines how the new built spaces both enabled and constrained the professional learning practices of academics. Drawing on a case study of the transition, the paper explores the ways in which the move to the new building disrupted existing ecologies of practices around professional learning, and how academics subsequently sought to establish new 'niches' to foster professional learning practices. The six study participants, who are also the authors and represent a range of career stages, made efforts to establish conditions for professional learning practices and a praxis of 'becoming an academic'. They did so by working with, around, and against the pre-figuring arrangements of the new built environment. The paper contributes to knowledge about how workspaces can disrupt and reconfigure the professional learning practices of educators. It addresses a gap in the literature on academics' professional learning in relation to changes in physical workspaces, making visible the ways in which academic practices are shaped by and shape new arrangements for professional learning in response to the built environment.